This is not a border reportage & reflection from the Palestine Festival of Literature - Soueif, Ahdaf 1950-; Hamilton, Omar Robert 1984- (Bloomsbury, 2017)
"Writers from Alice Walker to Michael Ondaatje to Claire Messud share their thoughts on one of the most vital gatherings of writers and readers in the world. The Palestine Festival of Literature was established in 2008 by authors Ahdaf Soueif, Brigid Keenan, Victoria Brittain and Omar Robert Hamilton. Bringing writers to Palestine from all corners of the globe, it aimed to break the cultural siege imposed by the Israeli military occupation, to strengthen artistic links with the rest of the world, and to reaffirm, in the words of Edward Said, "the power of culture over the culture of power." Celebrating the tenth anniversary of PalFest, This Is Not a Border is a collection of essays, poems, and sketches from some of the world's most distinguished artists, responding to their experiences at this unique festival. Both heartbreaking and hopeful, their gathered work is a testament to the power of literature to promote solidarity and hope in the most desperate of situations."...
Includes bibliographical references and index
Keywords: Palestine Festival of Literature; Geschichte; Arab-Israeli conflict -- Literature and the conflict; Arab-Israeli conflict -- Literary collections; Authors -- Political and social views; Literature and society; Literatur; Palästinensische Autonomiegebiete; Aufsatzsammlung